2011
DOI: 10.2147/ijn.s23845
|View full text |Cite
|
Sign up to set email alerts
|

SERS-based nanobiosensing for ultrasensitive detection of the p53 tumor suppressor

Abstract: Background One of the main challenges in biomedicine is improvement of detection sensitivity to achieve tumor marker recognition at a very low concentration when the disease is not significantly advanced. A pivotal role in cancer defense is played by the p53 tumor suppressor, therefore its detection with high sensitivity may contribute considerably to early diagnosis of cancer. In this work, we present a new analytical method based on surface-enhanced Raman spectroscopy which could significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 56 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Following Domenici et al ., the AuNPs were added 1:1 to a 4ATP solution in ethanol 45 . The 4ATP final concentration (0.01 g/l) was in large excess with respect to the minimum needed to achieve a full coverage of the AuNP surfaces (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Following Domenici et al ., the AuNPs were added 1:1 to a 4ATP solution in ethanol 45 . The 4ATP final concentration (0.01 g/l) was in large excess with respect to the minimum needed to achieve a full coverage of the AuNP surfaces (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…But until now, the direct effects of azurin protein on tumor markers of breast cancer (CEA, Muc1, and Krt20 genes) have not been studied. Domenici and co-workers described the specific interaction of p53 with azurin and they indicated that azurin can enter into the cancer cells and via forming a specific and stable complex with human p53 which leads to increase of tumor suppressor activity (Domenici et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The biomarker p53 was linked to a gold nanoparticle and captured for SERS detection with the protein azurin, which specifically reacts with p53. Even in human serum, p53 could be linked to the nanoparticle and specifically captured with azurin [105]. In another example, whole blood samples were purified to isolate albumin and globulin of gastric cancer patients via membrane electrophoresis before SERS analysis [14].…”
Section: Micro and Nano Particle Based Approachesmentioning
confidence: 99%